Nutrition Counseling for Pregnant Women, Rimba Soping Village, Padangsidimpuan Angkola Julu District in 2022 - Rya Anastasya Siregar; Novita Sari Batu Bara; Khoirunnisa Rangkuti (PT Inovasi Pratama Internasional, 2023)
Indonesia currently still has complex health problems. The degree of public health in Indonesia has not progressed significantly, even though there have been many programs to improve public health status that have been rolled out by the government. The degree of health is largely determined by the health of mothers and children, there are many factors that cause maternal and infant mortality, one of which is poor nutrition during pregnancy which causes complications during pregnancy and childbirth. Community service activities are carried out in residents' homes . Counseling was carried out for 1 (one) day, namely on April 17 2022, at 10.00 WIB until it was finished in Rimba Soping Village, Padangsidimpuan District, Angkola Julu . The material was delivered by providing counseling about the nutrition of pregnant women , then followed by providing snacks with the involvement of 4 DIII Midwifery study program students, Aufa Royhan Padangsidimpuan. Activity counseling which was carried out ran smoothly and was received enthusiastically by the participants as seen from the many pregnant women who asked about information about the nutrition of pregnant women and the participants also understood what should be consumed during pregnancy and the restrictions.